GENETIC DIVERSITY AND TRAIT ASSOCIATION ANALYSIS OF INDONESIAN RICE (Oryza sativa L.) GERMPLASM USING SSR MARKERS - Fatimah, Fatimah; Herlina, Lina; Silitonga, Tiur Sudiaty (SEAMEO BIOTROP, 2016)
Generating a new crop variety with certain desirable traits requires germplasm collection with wide genetic diversity to facilitate accelerated development of improved cultivars. This study was conducted to characterize genetic diversity of Indonesian rice accessions using SSR markers and their agro-morphological characters to allow the identification of Marker Trait Association (MTA). A survey of genetic diversity among 72 traditional landraces of 15 provinces in Indonesia and 24 improved varieties was conducted using four multiplex panels of 14 fluorescent-labeled SSR markers and 22 agro-morphological characters. A total of 140 alleles with an average of 10 alleles per locus and Polymorphism Information Content (PIC) values at 0.73. The population structure identified five subgroups. A total of 4 highly significant MTA were identified. One character with highly significant MTA was number of panicle associated with RM277. Based on SSR marker, RM105 had two MTAs for auricle color and ligule shape. After validation, these MTAs may be deployed to improve rice productivity.